PEMBANGUNAN PERTANIAN: ANTARA PERTUMBUHAN EKONOMI DAN KEBERLANJUTAN - Husodo, Sapto (Jurnal Ilmu-Ilmu Pertanian, 2015)
The agricultural sector has the heavy burden of being perceived as levers of national economic growth. As a consequence, to pursue short-term interests of many agricultural development practices carried out by ignoring the preservation aspects of natural resources. These conditions raise awareness about the importance of conserving natural resources as a factor of production increase agricultural productivity. Agricultural development should be directed through the right strategy with not merely the pursuit of economic growth, but by taking into account aspects of sustainability of agricultural resources. Therefore, it is time for the government continuously campaign and implement approaches to agricultural development that is integrated, environmentally friendly, efficient, sustainable, future-oriented and long-term.